New records of fossil bird bones from the Neogene in Hungary - Horváth, Ida (Zootaxa, 2025)
This paper presents previously unreported fossil bird bones from the Hungarian Neogene. They derive from seven sites as follows: Beremend 26 and 38, Egyházasdengeleg, Hidas and Máriahalom. The Early Miocene is represented by four new fossils from Máriahalom, with taxa and numbers of specimens as follows: Pandion pannonicus [1], Gruidae gen. et sp. indet. [1], Passeriformes sp. indet. [2]. Two fossils derive from one Middle Miocene sites as follows: Hidas (Aves sp. indet.. Two fossils come from Late Miocene sites: Alsótelekes (Aves indet.) and Egyházasdengeleg (Aves sp. indet.). A further 17 fossil bird bones are reported from the Pliocene Beremend sites 26 and 38 and represent 10 taxa (Aquila, Palaeocryptonyx, Palaeortyx, Tetrao, Cuculus, Surnia, Corvus, Muscicapidae, Turdidae, 2 Passeriformes, and 2 Aves indet.). These fossils provide records of 10 new taxa to the Hungarian Neogene avifauna.